The Implications of Islamic Public Finance in Indonesia: Integrating Zakat and Taxes for Public Welfare - Anggita Nurcahyani; Asmi Lidya Pradipta Rahayu; Muadz; Mawaddatul Ulya; Yusnina Hilyawati (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Public finance from an Islamic perspective is based on the purpose of Muslim life and the urgency of the role of the state in Islamic society. Indonesia as a country with a majority Muslim population has a role to manage public finance fairly and equitably. The source of state revenue is obtained from taxes, but in terms of Islamic public finance, people also should pay zakat. This study discusses the implementation of zakat and taxes as public finance in Indonesia, using descriptive qualitative methods with literature study analysis. In practice, zakat and tax have a relationship for public welfare but differ in terms of distribution. The distribution of zakat funds for the benefit of Muslims is a sign of gratitude to Allah. While the use of taxes to finance the general expenses of the state.